We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
255
2
avatar

\(f(x) = {x^2 -6x+5}\)

i have no clue on what to do... please show step by step on how you did it! :)

 May 6, 2018
 #1
avatar+101768 
+1

\(y=x^2-6x+5\\ x^2-6x=y-5\\ x^2-6x+9=y-5+9\\ (x-3)^2=(y+4)\\ vertex(3,-4)\)

.
 May 6, 2018
 #2
avatar+101768 
0

If you do not understand one of the steps, explain what your problem is the best you can and then I, or someone else, will help you more :)

Melody  May 6, 2018

20 Online Users

avatar
avatar